Sonographic Diagnosis of Complicated Cholecystitis. (30th October 2015) - Shapira-Rootman, Mika; Mahamid, Ahmad; Reindorp, Nadir; Nachtigal, Alicia; Zeina, Abdel-Rauf
Abstract : Objectives: Early detection of the complications of cholecystitis is important for clinical management, yet only a small percentage of patients have a correct diagnosis before surgery. The purpose of our study was to identify sonographic findings that are associated with complicated cholecystitis. Methods: Sonographic, surgical, and pathologic reports were reviewed for 70 patients who underwent early cholecystectomies from January 2010 to August 2014. Sonograms were assessed for 16 independent variables. Statistical analyses were performed to evaluate associations between various sonographic features and complicated cholecystitis. Results: Sonographic signs associated with complicated cholecystitis ( P < .05) were a greater short‐axis gallbladder diameter (mean, 4.4 versus 4.0 cm), a greater mean wall thickness (5.6 versus 4.2 mm), and the likelihood of wall striations, gallbladder echogenic content, pericholecystic free fluid, and local inflammatory fat changes. Specific sonographic signs, such as sloughed intraluminal membranes, were detected in a small percentage of cases (10%). None of the sonographic features evaluated in this study was found to be sensitive and specific enough to indicate complicated cholecystitis. In most cases, sonograms reflected severe inflammation, with multiple sonographic signs. Conclusions: Although multiple sonographic signs are associated with complicated cholecystitis, none of them is sensitive and specific enough to definitively diagnose it. Sonograms usually reflect severe inflammation, with numerous sonographic signs. Thus, in the right clinical context, sonograms of severe cholecystitis should alert radiologists to the possibility of complications.